A local current based iterative physical optics method for computing the RCS of target above sea surface. (January 2023) - Cong, Zhou; He, Zi; Taiping, Sun; Ding, Dazhi; Chen, Rushan
Abstract: A local current based iterative physical optics (LC-IPO) scheme, for the analysis of the scattering from large complex targets on sea surface, is proposed. By employing ray tracing mechanism, the current radiation iterations are limited to local region and performed for each "bounce" in the IPO scheme. This approach alleviates the need for expensive computation of simulations. Meanwhile, the resulting method makes use of field integrals which are accelerable using a fast multiple method algorithm. GPU acceleration technique is also used to accelerating the scattering analyzing. Numerical examples illustrate that the accelerated local current technique can greatly improve the computational efficiency of the iterative physical optics method, and the accuracy is as good as the previous method without acceleration.